2019
DOI: 10.1111/ijfs.14201
|View full text |Cite
|
Sign up to set email alerts
|

Aleurone cells are the primary contributor to arabinoxylan oligosaccharide production from wheat bran after treatment with cell wall‐degrading enzymes

Abstract: Summary Arabinoxylans and in particular arabinoxylan oligosaccharides (AXOS) from wheat are recognised for their prebiotic potential. A high‐yield, non‐chemical production of AXOS is therefore of interest when producing functional foods. This study investigated the enzymatic production of AXOS from wheat bran with the aim of establishing the main fraction contributing to production of AXOS. Fractions of wheat bran, outer pericarp and aleurone with two different purities were treated with the cell wall‐degradin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Ferulic acid (FA), the most abundant phenolic compound in WB, has shown antioxidant, anti-inflammatory, antihypertensive, and anti-arteriosclerotic effects in vitro and in vivo [ 9 ]. The accumulated scientific evidence of health benefits exerted by FA have promoted the interest of researchers to explore the potential use of WB as a resource in the production of functional ingredients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ferulic acid (FA), the most abundant phenolic compound in WB, has shown antioxidant, anti-inflammatory, antihypertensive, and anti-arteriosclerotic effects in vitro and in vivo [ 9 ]. The accumulated scientific evidence of health benefits exerted by FA have promoted the interest of researchers to explore the potential use of WB as a resource in the production of functional ingredients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining AXOS by enzymatic processes is of particular interest when producing functional foods since they are considered free of chemicals. Usually enzymes such as cellulases, β-glucanases and xylanases are involved in the solubilisation of arabinoxylans in wheat bran, aleurone fraction and outer pericarp fraction so that high yields are achieved [94]. Vangsøe, Sørensen and Bach Knudsen [94] noticed a substantial contribution of aleurone fraction to the production of AXOS in wheat bran.…”
Section: Dietary Fibres Extracted From Cereal Processing By-productsmentioning
confidence: 99%
“…Usually enzymes such as cellulases, β-glucanases and xylanases are involved in the solubilisation of arabinoxylans in wheat bran, aleurone fraction and outer pericarp fraction so that high yields are achieved [94]. Vangsøe, Sørensen and Bach Knudsen [94] noticed a substantial contribution of aleurone fraction to the production of AXOS in wheat bran. It was observed that among the structural features of the arabinoxylans, the A/X ratio affects the yield of AXOS [94].…”
Section: Dietary Fibres Extracted From Cereal Processing By-productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vangsøe et al . () achieved the highest yield of arabinoxylan oligosaccharides, the carbohydrates with health‐promoting potential, from aleurone layer among different fractions of wheat bran by using xylanase along with β‐glucanase and cellulase treatment. Due to the high water absorption capacity and viscosity arabinoxylan presented, xylanases were added to dough system to improve dough‐processing properties and bread characteristics.…”
Section: Introductionmentioning
confidence: 99%